1978
DOI: 10.1042/bj1710149
|View full text |Cite
|
Sign up to set email alerts
|

Studies on cathepsin B in human articular cartilage

Abstract: The thiol proteinase cathepsin B (EC 3.4.22.1), previously called cathepsin B1, was assayed in human articular cartilage by its hydrolysis of the synthetic substrate alpha-N-benzoyl-DL-arginine 2-naphthylamide. The enzyme was activated by cysteine and EDTA and completely inhibited by iodoacetamide and HgCl2. It was also partially inhibited by whole human serum. Human osteoarthrotic cartilage had increased activity when compared with normal cartilage. Cathepsin B activity of normal cartilage was age-related, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…The highly destructive cysteine peptidase cathepsin B is up-regulated in some pathologic states, including tumor invasion (1,2), rheumatoid arthritis (3,4), and osteoarthritis (OA) (5)(6)(7)(8). Cathepsin B, a marker of the dedifferentiated chondrocyte phenotype (9), is secreted by these cells in a dynamic, reversible mode bound to cell viability and protein synthesis (10).…”
mentioning
confidence: 99%
“…The highly destructive cysteine peptidase cathepsin B is up-regulated in some pathologic states, including tumor invasion (1,2), rheumatoid arthritis (3,4), and osteoarthritis (OA) (5)(6)(7)(8). Cathepsin B, a marker of the dedifferentiated chondrocyte phenotype (9), is secreted by these cells in a dynamic, reversible mode bound to cell viability and protein synthesis (10).…”
mentioning
confidence: 99%
“…However, in view of the demonstrated dependence of articular cartilage collagenase and proteoglycanases on metallic cations (1,3,6,10,11,13,15,18,21,22), the increased levels of these enzymes in osteoarthritis (4,10), and the suggestive results of this study, it seems that chemotherapeutic approaches aimed at enzyme inhibition would be worth studying.…”
Section: Figmentioning
confidence: 77%
“…This enzyme is not active at neutral pH (20). In the case of cathepsin B, Bayliss (1) has shown that it is more active in the presence of EDTA.…”
Section: Figmentioning
confidence: 97%
“…IL-l has been implicated in the pathogenesis of osteoarthritis [32] and has been localized in human osteoarthritic synovium as well as cartilage [33], thus suggesting a role of inflammation in the pathophysiology of osteoarthritis. However, other aspects of osteoarhritis, such as the switch from collagen type II to type I synthesis [22] and the production of cathepsin B [23,34], we believe can now be ascribed to phenotypic changes on the part of the chondrocytes rather than to IL-l stimulation (see Table I). It is thus possible that these two routes of chondrocyte activation in osteoarthritis either coexist or that they represent episodes occurring independently at different times during the development of the disease.…”
Section: Resultsmentioning
confidence: 99%